PENGARUH SERVICE QUALITY, SATISFACTION, STICKINESS, DAN USAGE INTENTION PADA PENGGUNAAN APLIKASI WHATSAPP DI SURABAYA - Lisa Nuri Safitri; Dudi Anandya; Silvia Margaretha (CALYPTRA, 2018)
The purpose of this research is to understand and analyze the influenceof service quality, satisfaction, stickiness toward usage intentionon the application of WhatsApp in Surabaya. Data processing was conducted using software SPSS AMOS 20. The sampling technique thatused is non-probability sampling. 150 respondents, who qualify the specified characteristics of the population were the total of sample used in this research whichdistributed by off line quetionaire. The result of this research that there was a positive influence betweenenvironment quality on satisfaction, a positive influence between outcome quality on satisfaction, a positive influence between satisfaction on usage intention, a positive influence between satisfaction on stickiness, a positive influence between stickiness on usage intention and mediating role of stickiness between satisfaction and usage intention is confirmed.